The Effect of Active Knowledge Sharing Strategy on Cognitive Learning Outcomes and Students' Learning Activities on Chemical Bonding Material - Dyah Khairunnisa; Ayu Rahmi; Agus Muliaman (Electronic Journal of Education, Social Economics and Technology, 2025)
This research is an Active Knowledge Sharing Strategy in learning chemical bonds to examine its effect on cognitive achievement and learning activities of students. This strategy encourages students to be active subjects in the learning process, not just recipients of information. Quantitative approach with Intact Group Comparison design was used at SMAS Syamsuddhuha in the odd semester of the 2024/2025 academic year. The sample was taken purposively by considering certain characteristics: each class consisted of 20 students. The research instruments consisted of 16 multiple choice questions and observation sheets that had been tested for validity, reliability, difficulty level, and differentiation. The results showed that the experimental class using active knowledge sharing strategy had an average cognitive achievement of 72.50 far above the control class which reached 56.25. In terms of learning activities, the experimental class achieved an average score of 75.22 almost twice that of the control class of 40.47, indicating a statistically significant difference. Thus, the active knowledge sharing strategy proved to be effective in improving students' cognitive understanding and learning activities on chemical bonding materials.